Ministers and governments’ financial resources: Are members of key government committees taking from the rest and giving to themselves? - Nielsen, Peter Heyn (Politica, 2025)
Central cabinet committees constitute the core of Danish cabinets but are seldom subject to quantitative political science studies. In this article, I focus on individual ministers and their policymaking role depending on whether they are members of such committees or not. For the years 1995-2023, I examine whether the share of total public expenditures for certain portfolios increase if the responsible minister has been member of either the Finance Committee or the Coordination Committee. The analysis shows a significant positive effect for ministers’ membership in central cabinet committees – especially membership of the Finance Committee. This indicates that permanent committee members enjoy significantly better opportunities for making a political impact as ministers than their colleagues in the cabinet. The results contribute substantially to our understanding of ministers’ role in policymaking and cabinet decision making processes.